From Mine to Metropolis: A Systematic Review of Green Mining Innovations for Sustainable Urban Logistics - Samuel Darwisman; Heri Purwanto; Haerun Nisa; Jusuf Roni Siahaan; Azizi Dermawan (Dinasti Publisher, 2025)
Urban logistics contributes significantly to environmental degradation, challenging the achievement of Sustainable Development Goals. Concurrently, the green mining industry has developed robust technological innovations with potential applicability in urban contexts, yet this cross-sectoral knowledge transfer remains underexplored. This study aims to bridge this gap through a systematic literature review of 30 peer-reviewed articles to identify transferable technologies and the determinants influencing their implementation. The methodology followed the PRISMA guidelines, analyzing literature from Scopus and Web of Science and assessing their quality using the CASP checklist. Results reveal three key transferable domains: (1) fleet electrification, (2) autonomous systems, and (3) circular economy models. Key enablers include policy incentives and long-term economic benefits, while high initial capital expenditure and regulatory uncertainty are primary barriers. The primary contribution of this research is a novel conceptual framework that provides an actionable roadmap for policymakers to accelerate the decarbonization of urban freight by leveraging proven industrial innovations. This study offers significant practical implications for enhancing urban sustainability.